Windows 10 May 2019 update the missing manual - Pogue, David (O'Reilly Media, 2019)
The Windows 10 May 2019 Update adds a host of new and improved features to Microsoft's flagship operating system-and this jargon-free guide helps you get the most out of every component. This in-depth Missing Manual covers the entire system and introduces you to the latest features in the Windows Professional, Enterprise, Education, and Home editions. You'll learn how to take advantage of improvements to the Game Bar, Edge browser, Windows Online, smartphone features, and a lot more. Written by David Pogue-tech critic for Yahoo Finance and former columnist for The New York Times -this updated edition illuminates its subject with technical insight, plenty of wit, and hardnosed objectivity.
"The book that should have been in the box.". - Online resource; title from title page (viewed June 3, 2019)
Keywords: Microsoft Windows (Computer file) -- Handbooks, manuals, etc; Microsoft Windows (Computer file); COMPUTERS; Networking; General; handbooks; Handbooks and manuals; Guides et manuels; Handbook